Analysis of the opportunities of motor stimulation in home environment in the central region of Rio Grande do Sul - SOARES, Ellen Santos; FLORES, Fábio Saraiva; KATZER, Juliana Izabel; VALENTINI, Nadia Cristina; CORAZZA, Sara Teresinha; COPETTI, Fernando (Brazilian journal of physical education and sport, 2015)
This study aimed to analyze the quality of home environments in the central region of Rio Grande do Sul to the occurrence of motor stimulation opportunities. Participants were 410 children aged between 18 and 42 months. For the assessment of home environments we used the Affordances in the Home Environment for Motor Development Self-Report - (AHEMD-SR). This instrument addresses the quality and quantity of factors of home environment that can enhance children's motor development. Descriptive analysis, t tests for independent samples and ANOVA were used to compare means. Data analysis showed that households with lower wages (p = 0.00) and whose parents have lower education (p = 0.00), have home environments that provide fewer opportunities for motor stimulation to children. The results were less satisfactory in relation to the provision of materials that encourage and stimulate children's motor development, on the external space of the residences (between 64,4% and 65,1% is classified as a very poor). It is concluded that there is a shortage in supply of materials that promote the stimulation of motor development in children, in most residences evaluated. The study provides strong evidence that these restrictions result from low socioeconomic and educational level of the families surveyed.